Spatial driving forces of dominant land use/land cover transformations in the Dongjiang River watershed, Southern China - Gao, Changjun; Zhou, Ping; Jia, Peng; Liu, Zhiyong; Wei, Long; Tian, Huiling (Environmental monitoring and assessment, 2016)
Information about changes in, and causes of, land use/land cover (LULC) is crucial for land use resource planning. We investigated the processes involved in LULC change (LUCC) in the Dongjiang Watershed, in Southern China, over a 15-year period to gain a better understanding of the causes of the main types of LUCC. Using a depth transition matrix and redundancy analysis (RDA), the major types and causes of LUCC for each LULC type over the past 15 years were identified. LUCC exhibited obvious net change, relatively low persistence, and high swap change. The swap changes in most LULC types were considered as a strong signal of LULC transformations. The driving forces behind swap changes were quantified and identified through RDA. The results showed that all driving forces played important roles in explaining swap changes of LULC, although the relative effects of these drivers varied widely with both LULC type and time period. Swap changes of the LULC types were generally classified into two categories. Some, e.g., built-up land and wetland, were affected mostly by landform and/or distance factors, while others, e.g., grassland and woodland, were modulated mostly by climate and/or socioeconomic factors. Selected spatial driving forces and local land use policies played important roles in explaining the dominant LUCC types, but on different timescales. These findings may improve understanding of the detailed processes involved in LUCC, landscape transformation, and the causes of LUCC in other areas with extensive LUCC and could help managers plan, design, and implement land resource management.
Gesehen am 11.05.2020